Study of association between polymorphisms in the PSMB5 (rs11543947) and PSMA3 (rs2348071) genes and multiple sclerosis in Latvians - Kalnina, J.; Paramonova, N.; Sjakste, N.; Sjakste, T. (Вiopolymers and Cell, 2014)
Functional realization of many signalling proteins and transcription factors implicated in the development and progression of multiple sclerosis is mediated by proteasomes. Aim of this case-control study was to evaluate genetic variations in the PSMB5 and PSMA3 genes encoding proteasomal subunits on the susceptibility to multiple sclerosis in Latvians. Methods. The rs11543947 (PSMB5) and rs2348071 (PSMA3) loci were genotyped in 291 multiple sclerosis patients and 305 healthy individuals and analysed general, subtype and sex-specific associations with the disease. Results. Loci rs11543947 and rs2348071 were identified as disease neutral and susceptible respectively. The rs2348071 heterozygous genotype GA showed strong main effect (P < 0.001; OR = 1.891, 95 % CI [1.360–2.628]), and moderate (P < 0.01; OR = 1.663, 95 % CI [1.152– 2.402]) and strong (P < 0.001; OR = 2.459, 95 % CI [1.534–3.943]) association with relapsing-remitting and secondary progressive phases of disease respectively. No genotype-sex interaction associated with multiple sclerosis has been detected. Conclusions. Our results suggest susceptibility of the rs2348071 heterozygous genotype to multiple sclerosis in Latvians. Протеасоми опосередковують виконання функцій багатьох сигнальних білків і факторів транскрипції, залучених до розвитку розсіяного склерозу. Мета. Оцінити можливу асоціацію генетичних варіантів генів PSMB5 і PSMA3 зі схильністю до захворювання на розсіяний склероз з-поміж жителів Латвії. Meтоди. Локуси rs11543947 (PSMB5) і rs2348071 (PSMA3) генотипували у 291 хворого на розсіяний склероз та у 305 здорових індивідів і оцінювали за асоціацією із захворюваністю на розсіяний склероз як такий, із підтипами хвороби і пов’язаною зі статтю асоціацією. Результати. Локус rs11543947виявився не пов’язаним з хворобою, а локус rs2348071 – асоційованим з нею. Гетерозиготний генотип ГА локуса rs2348071 тісно асоційований із захворюванням як таким (P < 0,001; співвідношення шансів (СШ) = 1,891; 95 % ДІ [1.360–2.628]), помірно асоційований (P < 0,01; СШ = 1,663; 95 % ДІ [1,152–2,402]) з ремітуючо-рецидивуючою формою захворювання та сильно (P < 0,001; СШ = 2,459; 95 % ДІ [1,534–3,943]) – зі вторинно прогресуючою формою. Пов’язаної з хворобою взаємодії між статтю і генотипом суб’єкта не відмічено. Висновки. Наші результати вказують на те, що жителі Латвії з гетерозиготним генотипом rs2348071 схильні до захворювання на розсіяний склероз. Протеасомы опосредуют выполнение функций многих сигнальных белков и факторов транскрипции, вовлеченных в развитие рассеянного склероза. Цель. Оценить возможную ассоциацию генетических вариантов генов PSMB5 и PSMA3 с подверженностью заболеванию рассеянным склерозом среди жителей Латвии. Meтоды. Локусы rs11543947 (PSMB5) и rs2348071 (PSMA3) генотипировали у 291 больного рассеянным склерозом и у 305 здоровых индивидов и оценивали по ассоциации с заболеваемостью рассеянным склерозом как таковым, подтипами болезни и связанной с полом ассоциации. Результаты. Локус rs11543947 оказался не связанным с болезнью, а локус rs2348071 – ассоциированным с заболеванием. Гетерозиготный генотип ГА локуса rs2348071 тесно ассоциирован с заболеванием как таковым (P < 0,001; отношение шансов (ОШ) = 1,891, 95 % ДИ [1.360–2.628]), умеренно (P < 0,01; ОШ = 1,663, 95 % ДИ [1,152–2,402]) – с ремиттирующе-рецидивирующей формой заболевания и сильно (P < 0,001; ОШ = 2,459, 95 % ДИ [1,534–3,943]) – со вторично прогрессирущей формой. Связанного с болезнью взаимодействия между полом и генотипом субъекта не отмечено. Выводы. Наши результаты указывают на подверженность жителей Латвии с гетерозиготным генотипом rs2348071 заболеваемости рассеянным склерозом.